Molecular Neurobiology of Addiction Recovery The 12 Steps Program and Fellowship - Blum, Kenneth. (SpringerBriefs in Neuroscience, 2013)
Humans are biologically programmed to seek out pleasurable experiences. These experiencesare processedin themesolimbic system, also referred to as the"reward center" of the brain, where a number of chemical messengers work in concert to provide a net release of dopamine in the Nucleus Accumbens.In some genetically predisposed individuals, addiction occurs when the mechanisms of the mesolimbic system are disrupted by the use of variousdrugs of abuse. Since Alcoholics Anonymous was founded in 1935, it's 12 step program of spiritual and character development has helped countless alcoholics and drug addictscurb their self-destructive behaviors. However, theprogram was developed at a time whencomparatively little was known about the function of the brain andit hasnever been studied scientifically.This is the first book to take a systematic look at the molecular neurobiology associated with each of the 12 steps and to review the significant body of addiction research literature that is pertinent to the program.